MENINGKATKAN KOMPETENSI GURU DALAM MENCIPTAKAN PEMBELAJARAN DINAMIS DAN KREATIF MELALUI PELATIHAN INOVATIF - Idrus, Idrus; Alaydrus, Siti Hadija; Laki, Ridwan; Ulfah; Yamin, Novita Salwa Partiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study employed a descriptive qualitative approach to explore the impact of training on teachers' instructional practices. Data were collected through structured and in-depth interviews, as well as direct classroom observations. A total of 15 teacher representatives who had participated in the training served as the study’s participants. To identify recurring patterns and central themes related to changes in the learning process after the training, the collected data were analyzed using thematic analysis techniques. The findings revealed that innovative training had a positive effect on teachers' competencies, particularly in mastering educational technology, applying interactive learning methods, and enhancing communication skills with students. Moreover, teachers demonstrated improved abilities in designing learning activities that are adaptive to students' needs. These findings underscore the importance of innovative training in supporting educational transformation in the digital era. It is recommended that such training be conducted on a continuous basis to strengthen teachers' professional capacity and to implement more effective and engaging teaching and learning processes for students